2020
DOI: 10.1002/dneu.22742
|View full text |Cite
|
Sign up to set email alerts
|

Resting‐state networks of the neonate brain identified using independent component analysis

Abstract: Resting‐state functional magnetic resonance imaging (rs‐fMRI) has been successfully used to probe the intrinsic functional organization of the brain and to study brain development. Here, we implemented a combination of individual and group independent component analysis (ICA) of FSL on a 6‐min resting‐state data set acquired from 21 naturally sleeping term‐born (age 26 ± 6.7 d), healthy neonates to investigate the emerging functional resting‐state networks (RSNs). In line with the previous literature, we found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 80 publications
3
9
0
Order By: Relevance
“…Our results in full-term neonates resonate with previous studies that observed high-order networks in this group. 40 , 45–47 , 84 Our results are also consistent with some brain structural studies, suggesting that fundamental structural features of the adult brain are already present in neonates from birth. For example, the white matter microstructure, a putative neural basis for information processing speed and intelligence in adults, is present in very early life.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results in full-term neonates resonate with previous studies that observed high-order networks in this group. 40 , 45–47 , 84 Our results are also consistent with some brain structural studies, suggesting that fundamental structural features of the adult brain are already present in neonates from birth. For example, the white matter microstructure, a putative neural basis for information processing speed and intelligence in adults, is present in very early life.…”
Section: Discussionsupporting
confidence: 91%
“…Although some previous studies have observed high-order networks in neonates, 40 , 45–47 , 84 others have not. 38 , 39 , 42 This inconsistency is likely due to methodological differences in the type of data acquired and the analyses method.…”
Section: Discussionmentioning
confidence: 87%
“…However, less is known about its roles, functional connectivity, and brain‐behaviour functions in neonates, especially across different states of wakefulness and sleep. Although neonates display a robust functional brain organization at birth (Rajasilta et al, 2020), the functional connectivity of these networks greatly differ from the mature networks in adults (Fitzgibbon et al, 2020), which is likely in part because of the fact that they are asleep (Horovitz et al, 2009). For example, adults scanned at rest have considerably higher fALFF values in the mPFC than neonates scanned during sleep (Huang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…60 min was the maximum duration of the complete scanning protocol, and total duration of the visit was less than 2 h. The data are still being processed and analyzed, but the current success rates are 125/180 for structural T1 and T2 scans (69%) (Acosta et al, 2020a), 172/180 (95%) for at least 20 good quality diffusion weighted images out of the acquired 96 images (N = 157 for 30 directions, N = 142 for 40 directions and N = 121 for 60 directions) (Merisaari et al, 2019). Success rates for task fMRI are 10/13 (77%) in preliminary findings (Tuulari et al, 2019) and 21/28 (75%) for the resting state data (Rajasilta et al, 2020). Unfortunately, we suffered from some technical difficulties with the T2-weighted images that were identified only after data collection, which significantly impacted the available good data from 92% estimated at the scanner to 69% in the final data.…”
Section: The Infant Scanning Procedures Of the Finnbrain Study And How To Calm Infants In The Scannermentioning
confidence: 99%